Perencanaan Sekretariat Lembaga Pemberdayaan Masyarakat Kelurahan Pahandut Seberang Kota Palangka Raya - Prasetyo Aminu; Charisma Chintiya Putri Saragih; Rista Nainggolan; Hilkya Bangun; Praza Putra Yudi; Hafiz Althaf; Noor Hamidah (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service activities through the Engineering for Building and Impact (TMB) program of the Faculty of Engineering, Palangka Raya University provide outputs on building designs in sub-districts or villages. TMB provides technical solutions in supporting infrastructure development, social facilities based on community participation. The focus of the activity is the technical design of the construction of the Secretariat of the Village Community Empowerment Institution (LPMK) based on the direction of the Village Head. The LPMK building functions as a community institutional center. The method uses qualitative methods including literature reviews, field observations, measurement surveys, interviews with village stakeholders, and the preparation of Detailed Engineering Design (DED) for spatial mapping of the Pahandut Seberang Village Area as well as LPMK drawing design using Auto-cad. The results of the activity show the preparation of technical documents for the LPMK Secretariat Office that are ready to be used as a reference for development, as well as increasing community capacity in understanding the infrastructure planning process. This activity shows that collaboration between students, the community, and the village government is able to produce technical outputs that are useful and sustainable for regional development.